2007
DOI: 10.4314/ejhd.v20i2.10021
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> anti-malarial activity of hydroalcoholic extracts from <i>Asparagus africanus</i> Lam. in mice infected with <i>Plasmodium berghei</i>

Abstract: Background: Malaria is a major public health problem in the world in general and developing countries in particular, causing an estimated 1-2 million deaths per year, an annual incidence of 300-500 million clinical cases and more than 2 billion people are at risk of infection from it. But it is also becoming more difficult to treat malaria due to the increasing drug resistance. Therefore, the need for alternative drugs is acute. Objective: This study aims at investigating the in vivo antiplasmodial activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 13 publications
17
54
0
Order By: Relevance
“…C NMR data indicated that the reaction took place at C-5 position, not at the C-2 position of embelin (1) and this might be due to steric factor that is apparent in the latter. Further confirmation of the reaction site was obtained from 13 C NMR data, where +8.06 ppm upfield shift of C-6 in 2 (d 94.15) was observed compared to that of the same carbon in 1 (d 102.21) due to high electron donating nature of the amine group. Thus, compound 2 was finally characterized as 5-(p-tolylamino)-2-hydroxy-3-undecyl-cyclohexa-2,5-diene-1,4-dione as indicated below.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…C NMR data indicated that the reaction took place at C-5 position, not at the C-2 position of embelin (1) and this might be due to steric factor that is apparent in the latter. Further confirmation of the reaction site was obtained from 13 C NMR data, where +8.06 ppm upfield shift of C-6 in 2 (d 94.15) was observed compared to that of the same carbon in 1 (d 102.21) due to high electron donating nature of the amine group. Thus, compound 2 was finally characterized as 5-(p-tolylamino)-2-hydroxy-3-undecyl-cyclohexa-2,5-diene-1,4-dione as indicated below.…”
Section: Discussionmentioning
confidence: 82%
“…The 13 C NMR spectrum of compound 1 revealed signals corresponding to 13 carbon atoms only, which does not fit with the number of carbons proposed in the molecular formula above. This is because oxygen bearing ring carbons of 2, 5-dihydroxy-3-alkyl-1,4-benzoquinones do not appear in the 13 C NMR spectrum because of fluxional effect caused by intra-molecular hydrogen bonding. This effect leads to long spin relaxation time which in turn leads to the saturation of oxygen-carbon signals as it was also indicated by Mahendran et al 15 Hence, compound 1 was unequivocally identified as the known compound embelin (1) In an attempt to improve the antimalarial activity of embelin (1), its aromatic amino derivatives (2-4) were semi-synthesized (Scheme 1) by using a one-step condensation reaction of embelin (1) with p-toluidine (5), o-toluidine (6) and aniline (7), respectively, and tested against mice infected with P. berghei parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Scientific Instrument). This was done every 24 h before each daily drug administration starting from the day prior to drug administration (Dikasso et al, 2006).…”
Section: In Vivo Pharmacodynamic Studiesmentioning
confidence: 99%